Molecular insights into the benefits of nicotine on memory and cognition - Alhowail, Ahmad (Mol Med Rep, 2021)
The health risks of nicotine are well known, but there is some evidence of its beneficial effects on cognitive function. The present review focused on the reported benefits of nicotine in the brain and summarizes the associated underlying mechanisms. Nicotine administration can improve cognitive impairment in Alzheimer's disease (AD), and dyskinesia and memory impairment in Parkinson's disease (PD). In terms of its mechanism of action, nicotine slows the progression of PD by inhibiting Sirtuin 6, a stress-responsive protein deacetylase, thereby decreasing neuronal apoptosis and improving neuronal survival. In AD, nicotine improves cognitive impairment by enhancing protein kinase B (also referred to as Akt) activity and stimulating phosphoinositide 3-kinase/Akt signaling, which regulates learning and memory processes. Nicotine may also activate thyroid receptor signaling pathways to improve memory impairment caused by hypothyroidism. In healthy individuals, nicotine improves memory impairment caused by sleep deprivation by enhancing the phosphorylation of calmodulin-dependent protein kinase II, an essential regulator of cell proliferation and synaptic plasticity. Furthermore, nicotine may improve memory function through its effect on chromatin modification via the inhibition of histone deacetylases, which causes transcriptional changes in memory-related genes. Finally, nicotine administration has been demonstrated to rescue long-term potentiation in individuals with sleep deprivation, AD, chronic stress and hypothyroidism, primarily by desensitizing α(7) nicotinic acetylcholine receptors. To conclude, nicotine has several cognitive benefits in healthy individuals, as well as in those with cognitive dysfunction associated with various diseases. However, further research is required to shed light on the effect of acute and chronic nicotine treatment on memory function.